1994
DOI: 10.1007/bf00178333
|View full text |Cite
|
Sign up to set email alerts
|

Unusual conformation of a 3?-thioformacetal linkage in a DNA duplex

Abstract: The DNA.DNA duplex d(CGCGTTSCH2OTTGCGC).d(GCGCAAAACGCG) (designated duplex III) containing a 3'-thioformacetal (3'-TFMA) linkage in the center of the sequence was characterized in detail by two- and three-dimensional homonuclear NMR spectroscopy. The NMR results were analyzed and compared with those of two duplexes of the same sequence: One is an unmodified reference sequence and the other contains a formacetal (OCH2O) linkage at the central T--T step (designated duplex I and duplex II, respectively). In gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 17 publications
5
38
0
Order By: Relevance
“…Region B and C ( Figure 5) are selected to start the sequential assignment. Region B is attractive to start the assignment of the deoxyribose strand, because no signals of the 2'-OMe RNA -:~~~~~~~~Q 4.i "-' 0i 8.0 6.0 4 0 2.0 Dl (ppm) Figure 5.…”
Section: Ocmentioning
confidence: 99%
“…Region B and C ( Figure 5) are selected to start the sequential assignment. Region B is attractive to start the assignment of the deoxyribose strand, because no signals of the 2'-OMe RNA -:~~~~~~~~Q 4.i "-' 0i 8.0 6.0 4 0 2.0 Dl (ppm) Figure 5.…”
Section: Ocmentioning
confidence: 99%
“…This mechanism can explain our earlier findings that the Vm~x values of DNA polymerization are sufficiently higher for many polymerases if ribooligonucleotides (or deoxyribooligonucleotides with the 3'-terminal ribonucleotide) have been used as a primer [31]. The A-like form is preferable for RNA-DNA hybrid duplexes [32,33] (and for some short duplexes which contains the ribonucleotide insertion [34]), hence the reverse B ~ A transition within the binding channel should have a lower energetic barrier in these cases. Mikita and Beardsley [35,36] have shown that DNA replication can be arrested by structural lesion of arabinosylcytosine in.…”
Section: Crawling Dnamentioning
confidence: 80%
“…The A-like form is preferable for RNA-DNA hybrid duplexes [32,33] (and for some short duplexes which contains the ribonucleotide insertion [34]), hence the reverse B ~ A transition within the binding channel should have a lower energetic barrier in these cases. Mikita and Beardsley [35,36] have shown that DNA replication can be arrested by structural lesion of arabinosylcytosine in.…”
Section: Crawling Dnamentioning
confidence: 99%
“…Such methods have been applied for the analysis of the NOEs of a 12-mer DNA duplex containing a GG mismatch 99 and for analysis of a modified 12-mer DNA duplex. 100 In both cases the 3D spectra clarified unusual NOEs, with important consequences for the geometry.…”
Section: Homonuclear 3d Nmr Of Dna and Rna Fragmentsmentioning
confidence: 99%
“…It has been demonstrated that 3D NOESY-NOESY spectra of good quality can be recorded for a 22-mer duplex. 11 Similarly, 3D NOESY-NOESY has been applied to a 40-base threestranded DNA junction, 101 where it allowed the completion of the proton assignments and confirmed the unusual geometry at the junction, and to a hybrid DNA-RNA dodecamer duplex, 102 where it resolved superimposed cross peaks of the RNA strand.…”
Section: Homonuclear 3d Nmr Of Dna and Rna Fragmentsmentioning
confidence: 99%